Implementasi Latihan Kader I Untuk Meningkatkan Nilai Tanggung Jawab Pada Kader Himpunan Mahasiswa Islam - adhapriadi, teza; Sanusi, Aris Riswandi; Repelita, Tridays (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2023)
This research aims to find out and examine the implementation of Cadre I Training for the Islamic Student Association carried out by the Buana Perjuangan University Commissariat in order to increase the values ​​of responsibility towards the cadres. This research uses a qualitative approach, with data obtained through interviews, observation and documentation studies. The data analysis technique used in this research is data reduction, displaying results, and drawing conclusions. The research results stated that at LK I HMI there were two levels of training, namely general and special, participants were provided with knowledge with local content and five mandatory materials which included HMI History, Basic Values ​​of Struggle, Constitution, Mission and Organizational Management Leadership. In its implementation, HMI UBP Karawang experienced obstacles in the form of budget and presenters who were considered still conservative and there were elements of HMI UBP Karawang that prioritized quantity and quality.